The Effectiveness of STP Strategy in Enhancing the Competitiveness of Educational Services at the Integrated Islamic Boarding School Al-Multazam - Mumun Munawaroh; Aris Aris; Amar Qulbi; Mohammad Irfan Rosviana (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
This study aimed to analyze the effectiveness of implementing the Segmentation, Targeting, and Positioning (STP) strategy in enhancing the competitiveness of educational services at the Integrated Islamic Boarding School Al-Multazam. This research employed a mixed-methods approach, utilizing a case study method, focusing on parents' perceptions of the competitiveness of the boarding school. Quantitative data were collected through questionnaires distributed to parents of students to gauge their perceptions of the STP strategy dimensions and the competitiveness of the Islamic Boarding School. Qualitative data were obtained through in-depth interviews, field observations, and documentation to strengthen the quantitative findings. Data analysis was conducted using descriptive and quantitative methods to evaluate the implementation of the STP strategy applied by the boarding school. The results showed that the STP strategy plays a significant role in shaping parents' positive perceptions of the competitiveness of the Integrated Islamic Boarding School Al-Multazam, particularly in attracting prospective students and maintaining parents' trust. This study recommends further development of STP-based marketing strategies to enable the boarding school to compete more effectively in the education sector. Keywords: STP Strategy, Competitiveness, Educational Services, Islamic Boarding School, Al-Multazam